2022
DOI: 10.3390/ijms23137093
|View full text |Cite
|
Sign up to set email alerts
|

Arabinoxylan and Pectin Metabolism in Crohn’s Disease Microbiota: An In Silico Study

Abstract: Inflammatory bowel disease is a chronic disorder including ulcerative colitis and Crohn’s disease (CD). Gut dysbiosis is often associated with CD, and metagenomics allows a better understanding of the microbial communities involved. The objective of this study was to reconstruct in silico carbohydrate metabolic capabilities from metagenome-assembled genomes (MAGs) obtained from healthy and CD individuals. This computational method was developed as a mean to aid rationally designed prebiotic interventions to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…Another taxon that correlated positively with the sow fecal score was Paraprevotella xylaniphila . This species has been reported to produce succinate by fermentation 48 , and its assembled genome contained multiple xylan- and pectin-hydrolyzing enzymes, which is consistent with the report of Sabater et al 49 . identifying similar enzymes in the genome of the strain Paraprevotella xylaniphila YIT 11841.…”
Section: Discussionsupporting
confidence: 89%
“…Another taxon that correlated positively with the sow fecal score was Paraprevotella xylaniphila . This species has been reported to produce succinate by fermentation 48 , and its assembled genome contained multiple xylan- and pectin-hydrolyzing enzymes, which is consistent with the report of Sabater et al 49 . identifying similar enzymes in the genome of the strain Paraprevotella xylaniphila YIT 11841.…”
Section: Discussionsupporting
confidence: 89%
“…Our results demonstrate a significant contribution of AP-diet to reduce intestinal inflammation in a DSS-induced colitis model, reflected by a delayed increase of DAI, reduced promotion of pro-inflammatory TNFα, reduced histological inflammation scores and modification of the overall gut microbiota composition and SCFA production. These results provide an experimental demonstration that pectin containing prebiotic ingredients can be metabolized, to a certain extent, by the disrupted microbiome in colitis models, as previously suggested through in silico 18 and in vitro investigations. 17 It should be noted that despite its content in prebiotic pectins, the apple pomace, as incorporated in the animals feed, is a complex mixture of ingredients; 16 hence, the possibility that other apple pomace components may be affecting the inflammatory response observed in the animals cannot be ruled out.…”
Section: Discussionsupporting
confidence: 78%
“…Besides, a prior in silico study based on comparative analyses of predicted carbohydrate utilizing activities in the gut microbiome of healthy vs. IBD patients revealed that despite the important gut microbiota shifts encountered in IBD patients, pectin degraders are still represented in most metagenomes. 18 Thus, these results encouraged us to evaluate in vivo the potential beneficial effects of pectin-rich apple pomace as a dietary ingredient. To this end, a basal rodent diet was supplemented with 10% dried apple pomace, an amount that has already been reported to confer metabolic effects in other rodent models 45 and which, in our case, is expected to provide sufficient pectin components to exhibit effects on the microbiome 46 (ESI Table S1†).…”
Section: Discussionmentioning
confidence: 99%
“…Metage2Metabo integrates such analyses together with GENRE reconstruction to systematically compare the metabolic potential of metagenomic samples or genome collections (Belcour et al., 2020 ). Discrete models of this kind were used to screen microbial metabolic potentials (Ramalho et al., 2022 ), to predict potential symbiotic relationships between MAGs from patients with Crohn's disease and healthy individuals (Sabater et al., 2022 ) and to analyse metabolic complementarity (Karimi et al., 2021 ).…”
Section: Models For Large‐scale Metabolic Exploration Of Microbial Co...mentioning
confidence: 99%